توليف وتوصيف الجسيمات النانوية المعدنية بواسطة الشيتوزان - بن عمر إلهام (Univrsity Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى التعرف على أهم خصائص الجسيمات النانوية لأكاسيد المغنيسيوم والزنك النانوية المصنعة بإستخدام مختلف أنواع الشيتوزان (Pimelia payraudi latreille ، Blaps lethifera ، Pimelia fernandezlopezi و Musca domestica ،قشور السلطعون، قشور الجمبري وبكتيريا Streptomyces griseus)، تم تحليل مختلف أنواع الشيتوزان المستخرج و الجسيمات النانوية التي تم الحصول عليها بإستخدام التقنيات القياسية UV-Vis وFT-IR و DRX وSEM /EDX ،و تم أيضا تقييم أنشطتها المضادة للبكتيريا وإختبار مدى قدرة الشيتوزان على امتزاز صبغة أزرق الميثيلين، و كذا قدرة الجسيمات النانوية على تحلل ذات الصبغة . أظهرت هذه الدراسة، أن المردود للشيتوزان المعزول لمختلف الحشرات 0.1±39%، 0.3±50%، 0.5±41.7% و 0.2±57.9% لPimelia payraudi latreille ، Blaps lethifera ، Pimelia fernandezlopezi و Musca domestica على التوالي، و أظهرت مستخلصات الشيتوزان نشاطًا جيدًا مضادًا للبكتيريا بما في ذلك Listeria Innocua، Bacillus Subtiliis، Staphylococcus Aureus، Salmonella Typhimuruim و Pseudomonas Aeruginosa ، وتبين أن الشيتوزان يتمتع بقدرة امتزاز جيدة لصبغة أزرق الميثيلين، حيث أثرت درجة نزع الأسيتيل من الشيتوزان على امتزاز الصبغة، حيث كانت قدرة امتصاص الشيتوزان عالية عند زيادة قيمة درجة نزع الأستيل (DD) ، حيث كان شيتوزان من Pimelia payraudi latreille أعلى درجة نزع الأسيتيل (90%) ، كانت لديه قدرة امتزاز عالية بكفاءة إزالة 89% يليها الشيتوزان من Pimelia fernandezlopezi ، الشيتوزان من Blaps lethifera، و الشيتوزان من Musca domestica بنسبة87 و 37 و 26% على التوالي خلال 120 دقيقة. تم حصول على متوسط الحجم البلوري لـ MgO NPs حوالي 17، 43.1 و42.9 نانومتر، من الشيتوزان المصنع من خنفساء Pimelia payraudi latreille، قشور السلطعون، و قشور الجمبري على التوالي ، أما الحجم البلوري لـ ZnO NPs المحضر من الشيتوزان المصنع من خنفساء Pimelia payraudi latreille، قشور السلطعون، قشور الجمبري وبكتيريا Streptomyces griseus يساوي 29، 36.3،36.5و36.5نانومتر على التوالي، أظهرت الجسميات المصنعة تأثيرات جيدة لإزالة صبغة أزرق المثيلين حيث تم تحقيق تدهور بنسبة 60% و 56% و 44% ل ZnO NPs المحضر بواسطة الشيتوزان المستخرج من قشور الجمبري وقشور السلطعون وبكتيريا Streptomyces griseus على التوالي في غضون 60 دقيقة، في المقابل أظهر MgO NPs كفاءة التحلل الضوئي بنسبة 89 و77% على التوالي لـ MgO NPs المحضرة بإستخدام الشيتوزان من قشور الجمبري وقشور السلطعون في وقت قدره 120 دقيقة، وأظهرت النشاط المضاد للبكتيريا لـ ZnO NPs ضد البكتيريا موجبة الجرام مثل Bacillus subtilis و Staphylococcus aureus و Listeria innocua وضد البكتيريا سالبة الجرام مثل Pseudomonas aeruginosa و Salmonella typhimurium و كان النشاط المضاد للبكتيريا قوي لـ MgO NPs ضد البكتيريا ســــــــالبة الجرام (Salmonella typhimurium) ، ولكن لا يظهر أي تأثير واضح على البكتيريا موجبة الجرام، بإختصار يحمل تخليق الجسيمات النانوية القائمة على الشيتوزان وعدًا كبيرًا لمواجهة التحديات المعقدة في مختلف المجالات، ولكن البحث والتطوير المستمر ضروريان لإطلاق إمكاناته بالكامل وضمان استخدامه الآمن والفعال في التطبيقات العملية. َAbstract: This study aims to identify the key characteristics of nano-sized particles of magnesium and zinc oxides manufactured using various types of chitosan (Pimelia payraudi latreille, Blaps lethifera, Pimelia fernandezlopezi, and Musca domestica, shrimp shells, crab shells, and Streptomyces griseus bacteria. Various types of extracted chitosan and the nano-sized particles obtained were analyzed using standard techniques such as UV-Vis, FT-IR, DRX, and SEM/EDX. Additionally, their antibacterial activities were evaluated, as well as the chitosan's ability to adsorb methylene blue dye and the ability of the nano-sized particles to degrade the same dye. This study showed that the yield of isolated chitosan from different insects was 39±0.1%, 50±0.3%, 41.7±0.5%, and 57.9±0.2% for Pimelia payraudi latreille, Blaps lethifera, Pimelia fernandezlopezi, and Musca domestica, respectively. Chitosan extracts exhibited good antibacterial activity against bacteria including Listeria Innocua, Bacillus Subtilis, Staphylococcus Aureus, Salmonella Typhimurium, and Pseudomonas Aeruginosa. Chitosan also demonstrated good methylene blue dye adsorption capacity, with adsorption efficiency increasing with the degree of deacetylation (DD). The chitosan from Pimelia payraudi latreille had the highest deacetylation degree (90%) and exhibited a high adsorption efficiency of 89%, followed by the chitosan from Pimelia fernandezlopezi ، Blaps lethifera and Musca domestica with 87% and 37%, respectively, within 120 minutes. The average crystalline size of MgO NPs was approximately 17, 43.1, and 42.9 nanometers when manufactured from chitosan extracted from Pimelia payraudi latreille, shrimp shells, and crab shells, respectively. The crystalline size of ZnO NPs prepared from chitosan extracted from Pimelia payraudi latreille, shrimp shells, crab shells, and Streptomyces griseus bacteria was 29, 36.5, 36.3, and 36.5 nanometers, respectively. The manufactured particles showed effective removal of methylene blue dye, with degradation rates of 60%, 56%, and 44% for ZnO NPs prepared using chitosan extracted from crab shells, shrimp shells, and Streptomyces griseus bacteria, respectively, within 60 minutes. In contrast, MgO NPs exhibited 89% and 77% photocatalytic degradation efficiency for MgO NPs prepared using chitosan from crab shells ,and shrimp shells, respectively, within 120 minutes. Furthermore, ZnO NPs demonstrated strong antibacterial activity against gram-positive bacteria such as Bacillus subtilis and Staphylococcus aureus, as well as against gram-negative bacteria such as Pseudomonas aeruginosa and Salmonella typhimurium. MgO NPs exhibited strong antibacterial activity against Salmonella typhimurium but did not show a clear effect on gram-positive bacteria. In summary, the synthesis of chitosan-based nano-particles holds great promise for addressing complex challenges in various fields. However, continuous research and development are necessary to fully unleash their potential and ensure their safe and effective use in practical applications.
Synthesis and characterization of metal nanoparticles by chitosan
أطروحة دكتوراه تخصص هندسة كيميائية كلية التكنولوجيا جامعة الوادي
Keywords: النشاط المضاد للبكتيريا; صبغة أزرق الميثيلين; Chitosan; ZnO NPs; MgO NPs; Antibacterial activity; Methylene blue dye